Integration of Peer Instruction in the Guided Inquiry Learning Model: Practicing Science Literacy through Scratch - Faikotun Nikmah; Ellianawati Ellianawati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
The study is to determine the scientific literacy skills of students by using the peer-instruction integration learning model in guided inquiry through scratch media. The study was conducted at SMAN 14 Semarang in class x on circular motion material, and the research technique used was random sampling. The method used is an experiment with a one-shot case study design. The instrument used was an essay test to determine students' scientific literacy skills. The results show that the scientific literacy ability of students in the aspects of science as the body of knowledge is 30.3% with a low category, science as a way of thinking gets results that are 46.4% with a low category, science as a way to investigate obtaining results is 78.7% with enough category. The interaction between science technology and society gets results that are 50.5% with a low category. It can be concluded that overall the ability of scientific literacy has not been well trained, while the ability of scientific literacy in the scientific aspects as a way to investigate has been sufficiently trained.